2022
DOI: 10.1002/mrd.23556
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium nobile Lindl polysaccharides improve testicular spermatogenic function in streptozotocin‐induced diabetic rats

Abstract: Dendrobium nobile Lindl polysaccharides (DNLP) exhibited various biological functions. This study aimed to investigate the protective effects of DNLP on testicular spermatogenic function in streptozotocin (STZ)‐induced diabetic rats in comparison with metformin. The blood glucose level was significantly increased and the homeostatic model assessment for insulin resistance (HOMA‐IR) aggravated markedly in diabetic rats. The weight of testis and epididymis, and the sperm number and motility were decreased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The most relevant phytochemical elements in dendrobium species include polysaccharides, alkaloids, and polyphenols, and the bioactive components of dendrobium include gigantol, moscatilin, dendrofalconerol A, dendrochrysanene, crispidatin, confusarin, denbinobin, and chrysotobibenzyl [ 26 ]. Polysaccharides are among the main active components of dendrobium, exerting antioxidant, anti-inflammatory, and anti-apoptotic effects [ 27 , 28 , 29 , 30 ]. In this study, we found that the main active compounds of DFE were moscatilin, gigantol, and chrysotobibenzyl ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant phytochemical elements in dendrobium species include polysaccharides, alkaloids, and polyphenols, and the bioactive components of dendrobium include gigantol, moscatilin, dendrofalconerol A, dendrochrysanene, crispidatin, confusarin, denbinobin, and chrysotobibenzyl [ 26 ]. Polysaccharides are among the main active components of dendrobium, exerting antioxidant, anti-inflammatory, and anti-apoptotic effects [ 27 , 28 , 29 , 30 ]. In this study, we found that the main active compounds of DFE were moscatilin, gigantol, and chrysotobibenzyl ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that Dendrobium nobile-derived polysaccharides (DNP) could increase the activity of LDHA along with the production of lactate and have anti-apoptotic effects on spermatogenic cells, thereby improving testicular spermatogenic function in diabetic patients and animals. [61][62][63] What is more, our team has demonstrated that increased intake of ICA protected diabetic rats from high-fat diet and streptozotocininduced spermatogenesis abnormalities. [23] The present results also confirmed that the expression of apoptosis-related genes was increased, and the mRNA and protein expression level of LDHA, key enzymes related to glycolysis has reduced in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no evidence about the protective role of bezafibrate on diabetes-induced male spermatogenesis dysfunction. STZ injection-induced DM mice model can mimic the clinical features of patients with type 1 diabetes and has been used to employ diabetes-related male fertility in several previous studies [ [25] , [26] , [27] ]. Thus, this study was designed to investigate the effects of bezafibrate on testicular function using streptozotocin (STZ)-induced type 1 DM mice model and to discover the underlying molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%